PENGARUH KUALITAS LAYANAN,KEPUASAN DAN RELIGIUSITAS TERHADAP LOYALITAS NASABAH BANK SYARIAH MANDIRI CABANG BANDA ACEH - Raziq Aulia; Hafasnuddin Hafasnuddin (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
The purpose of this study was to determine the effect of Service Quality, Satisfaction and Religiosity on Customer Loyalty of Bank Shariah Mandiri branch of Banda Aceh. The sample used in this research was customers of Bank Shariah Mandiri branch of Banda Aceh with total 180 respondents. The data collection equipment used was questionnaire. This research used multiple linear regression analysis. The results showed that Service Quality, Satisfaction and Religiosity simultaneously affect on customer Loyalty, Service quality has a positive and significant effect on Customer Loyalty, Satisfaction has a positive and significant effect on customer Loyalty and Religiosity has a positive and significant effect on customer Loyalty. Keywords: Service Quality, Satisfaction, Religiosity, Customer Loyalty